ANALYSIS OF CASH SWIPE TRANSACTIONS IN THE FRAMEWORK OF ISLAMIC ECONOMIC LAW AND THEIR ALIGNMENT WITH SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Yunita Sari; Muthoifin; Amel Saib; Aboubacar Barry (Profetika: Jurnal Studi Islam, 2024)
This study aims to analyze the practice of cash swipe transactions conducted through various platforms and applications from the perspective of Islamic economic law and their alignment with the Sustainable Development Goals (SDGs). The research adopts a quantitative approach and relies on literature review as the primary method. Data sources include books, journals, and other relevant references that address the core issue. The findings indicate that cash swipe transactions represent a functional misuse of credit cards, originally intended as a means of payment for goods and services. In these transactions, individuals feign purchasing goods but instead withdraw cash, facilitated by stores offering such services. This practice constitutes a violation of ethical principles in Islamic business. From the perspective of Islamic economic law, cash swipe transactions are deemed haram (prohibited) because they involve dishonesty, fraud, and the element of riba (usury). Furthermore, such transactions foster unethical business practices aimed solely at maximizing profit through illicit means. These violations disrupt the integrity of economic transactions and contravene Islamic ethical guidelines, which prioritize fairness, transparency, and mutual benefit. In the context of the SDGs, cash swipe transactions undermine several goals, particularly Goal 8 (Decent Work and Economic Growth) and Goal 16 (Peace, Justice, and Strong Institutions). By promoting fraudulent activities and unethical practices, these transactions contribute to economic instability and erode trust in financial systems. Conversely, adherence to Islamic economic principles aligns with the SDGs by fostering ethical financial practices that promote sustainable economic growth, social justice, and institutional integrity. This study highlights the necessity of stricter regulations and public awareness to mitigate the risks associated with cash swipe transactions. Encouraging compliance with Islamic economic law not only preserves ethical standards but also supports global efforts toward achieving the SDGs.